(untitled) (World Science, 2018)
The article reveals the peculiarities of ventures investigated the sources of their funding. The problems of venture financing innovation enterprises of the agricultural sector. The problems and prospects of development of venture investment in Ukraine. Found that in Ukraine is a source of venture capital organizations, large companies and commercial banks. Today, almost every company has its own venture capital fund that invests in innovative businesses related fields. Unlike the developed foreign countries in Ukraine basic research in the agricultural sector financed only by the state. This fact provokes the creation of favorable conditions for attracting private and foreign investments for the development of research and innovation in agriculture.